The Influence of Service Quality on Customer Satisfaction in Islamic Rural Banks during the Covid-19 Pandemic: A CARTER Model - Alfitri Zukhrufani; Afifah Afifah; Firsty Izzata Bella (Jurnal Ilmiah Ekonomi Islam, 2022)
The Covid-19 virus has become a global pandemic and gave an adverse impact on various sectors including the financial sector. Islamic Rural Bank (BPRS) as a provider of financial services plays an essential to carry out the function of collecting and distributing funds for the economic development of the community. However, with the spread of the Covid-19 virus, BPRS is obliged to limit its services. This study aimed to investigate empirically the effect of service quality on customer satisfaction of BPRS Bangka Belitung during the Covid-19 period by utilizing the CARTER model consisting by six dimensions (compliance, assurance, reliability, tangibles, empathy, and responsiveness). The research method applied is the quantitative method using Multiple Regression Analysis as the technique of data analysis. Data was collected by distributing questionnaires and applying the Likert Scale as a variable measurement scale. A total of 77 questionnaires were collected using the purposive sampling technique with the characteristics of the respondents, namely customers who had used the services of BPRS Bangka Belitung during the Covid-19 pandemic. The results indicating that the dimensions of compliance and responsiveness influence significantly customer satisfaction during the Covid-19 pandemic, while the other dimensions show no significant effect on customer satisfaction.